(untitled) (Fiep Bulletin - online, 2015)
The objective of this study was to identify and analyze the main reasons that influenced non-athlete adolescents to begin the practice of swimming. In order to collect information for the study, a questionnaire was prepared and applied to a sample group made up of 98 non-athlete adolescents, in the age range between 13 and 18 years, of both sexes, who practice swimming in three specific establishments of teaching-learning and practicing swimming. The outcome of this research revealed that the main reasons that influenced the investigated group to begin the practice of swimming were their parents’ support, doctor’s orders, the pleasure and the personal fulfillment stemming from practicing swimming, the desire of learning to swim, and the need to improve their physical fitness.